The new generation of winter recreational and sports facilities on artificial relief in cities - Afonina, Marina; Shcherbina, Elena; Balakina, Alevtina (International Journal of Engineering and Technology, 2018)
Nowadays we observe a rapid growth of various new and actively developing facilities for winter sports and recreation. This paper is aimed at analyzing the structure of these facilities and establishing the dependence of their public popularity on the design, technology, environmental and economic efficiency. The main research methods are monitoring of the chosen facilities, data collection and summarizing, classifying and description. The key procedures and results include on-site investigations of the facilities, sociological surveys of their popularity, definition of the factors that hamper their development, working out and testing a mathematical model of climatic influence on attendance. It is shown that despite the growing demand for new sports and recreational centers, most Russian cities do not have the necessary natural conditions (elevations, complex relief) to satisfy the requirements of the contemporary winter sports enthusiasts. To meet this demand, artificial constructions for mountain and cross-country skiing, snowboarding, tubing and skating are set in parks, residential areas and on specially designated territories. In building theses facilities, various designs, constructions and technologies are used, which are considered in detail in this paper. We provide examples of successful recreational centers on artificially engineered reliefs well-blended with the Moscow urban area. We make a conclusion about the advantages of constructing new facilities and the necessity to fit them harmoniously into the existing natural and man-made environment. Temporary constructions for sports and recreation have minimal impact on the environment. At the same time, they give room for experimenting with forms, materials, technologies; they are flexible, mobile and relevant for cities. We characterize such facilities as nature-and-technology compatible systems. Our findings can be useful for specialists in urban planning and development, ecology, sociology, economics, sports and recreational management.Â